Magnetically Promoted Rapid Immunofluorescence Staining for Frozen Tissue Sections. (August 2019) - Onishi, Tatsuya; Matsuda, Sachiko; Nakamura, Yuki; Kuramoto, Junko; Tsuruma, Akinori; Sakamoto, Satoshi; Suzuki, Shunichi; Fuchimoto, Daiichiro; Onishi, Akira; Chikaki, Shinichi; Kaneko, Miki; Kuwahata, Akihiro; et al.
Current immunohistochemistry methods for diagnosing abnormal cells, such as cancer cells, require multiple steps and can be relatively slow compared with intraoperative frozen hematoxylin and eosin staining, and are therefore rarely used for intraoperative examination. Thus, there is a need for novel rapid detection methods. We previously demonstrated that functionalized fluorescent ferrite beads (FF beads) magnetically promoted rapid immunoreactions. The aim of this study was to improve the magnetically promoted rapid immunoreaction method using antibody-coated FF beads and a magnet subjected to a magnetic field. Using frozen sections of xenograft samples of A431 human epidermoid cancer cells that express high levels of epidermal growth factor receptor (EGFR) and anti-EGFR antibody-coated FF beads, we reduced the magnetically promoted immunohistochemistry procedure to a 1-min reaction and 1-min wash. We also determined the optimum magnetic force for the antibody reaction (from 7.79 × 10 −15 N to 3.35 × 10 −15 N) and washing (4.78 × 10 −16 N), which are important steps in this technique. Furthermore, we stained paraffin-embedded tissue arrays and frozen sections of metastatic breast cancer lymph nodes with anti-pan-cytokeratin antibody-coated FF beads to validate the utility of this system in clinical specimens. Under optimal conditions, this ultra-rapid immunostaining method may provide an ancillary method for pathological diagnosis during surgery. (J Histochem Cytochem 58:XXX–XXX, 2010)